2022
DOI: 10.1097/md.0000000000029624
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 of follicular fluid and outcome of in vitro fertilization

Abstract: The quality of an oocyte is influenced by its microenvironment, which includes cumulus cells and follicular fluid, as well as cells of the immune system and their products. The ovarian interleukins, which are secreted by the granulosa cells and other immune cells within the ovaries and follicles, regulate various functions between the cells. IL-6 is a cytokine that is present in the follicular fluid and may affect the quality of oocytes. There are some inconsistencies in the literature regarding the concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…Several studies have been conducted, but there is no conclusive answer regarding the role of IL-6 in oocytes and subsequent embryos. Higher concentrations of IL-6 in FF can either increase [41] or decrease [24] the pregnancy outcome in women. Supplementation of culture media with IL-6 improved fetal development of IVF-embryos in cows [42] and supported embryonic compaction, blastulation and hatching in mice [43].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been conducted, but there is no conclusive answer regarding the role of IL-6 in oocytes and subsequent embryos. Higher concentrations of IL-6 in FF can either increase [41] or decrease [24] the pregnancy outcome in women. Supplementation of culture media with IL-6 improved fetal development of IVF-embryos in cows [42] and supported embryonic compaction, blastulation and hatching in mice [43].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other studies have reported no correlation between IL-1β and IL-10 concentrations and the pregnancy rate [ 22 , 24 ]. Surprisingly, a recent study has even reported that the concentration of IL-6 in the follicular fluid is elevated in patients with confirmed pregnancy [ 31 ], thus highlighting the heterogeneity of the results in the literature. In this sense, the different stimulation protocols used during controlled ovarian stimulation may also play a role, since it has been established that gonadotrophin stimulation in IVF alters the immune cell profile in the follicular fluid and the cytokine concentrations in the follicular fluid and serum [ 32 ].…”
Section: Discussionmentioning
confidence: 99%